The analysis of the speech act by Van Dijk - Basal, Mohammad; Saied, Ferias (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The speech act theory started by the English language philosphor John Austin , who is considered as the father of linguistic , he was influenced by the language philospher Witginstain who thinks that the meaning is the usage, this theory had become the most important one in the last sixtys century uptill now , it is also still having more techniques and concepts to make it richer, moreover, this theory becomes a methology to analyse the speech act in all its types, in this field , the importance of the researches and the pragmatic studies which the Holandian Van Dijk restruct rely on the speech act theory.